2005
DOI: 10.1111/j.0011-1348.2005.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Disputes Involving Youth Street Gang Members: Micro‐social Contexts*

Abstract: This paper examines microsocial contexts of violent and nonviolent dispute-related incidents involving gang members. Data consist of reports of field observations of twelve black and eight white youth street gangs in Chicago between 1959 and 1962. Dispute-related incidents (N = 2,637) were classified according to three primary pretexts: normative or order violations, identity attacks and retaliation. Findings show that disputes associated with each of these generally unfolded consistently with expectations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 28 publications
7
82
0
1
Order By: Relevance
“…Many gang members also spend a great deal of their time engaged in conventional pursuits by taking steps to find a job, taking part in sports, and making plans for the future such as enlisting in the Navy (Hughes & Short, 2005). This research implies that many gang members are optimistic in their expectations for their futures and contrasts with the depressed outlook one might expect from working class youth who recognize that their chances of legitimate success are blocked by the unequal class system imposed on them.…”
Section: Theory Of Differential Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many gang members also spend a great deal of their time engaged in conventional pursuits by taking steps to find a job, taking part in sports, and making plans for the future such as enlisting in the Navy (Hughes & Short, 2005). This research implies that many gang members are optimistic in their expectations for their futures and contrasts with the depressed outlook one might expect from working class youth who recognize that their chances of legitimate success are blocked by the unequal class system imposed on them.…”
Section: Theory Of Differential Opportunitymentioning
confidence: 99%
“…There is also the possibility of social learning aspects to gang membership. Young boys look up to gang members, mimic them, and aspire to gang membership (Hughes & Short, 2005) and gang films depicting characters rewarded for gang-like behaviors act as a blueprint for young aspiring gang members (Przemieniecki, 2005). Consequently, youth may adapt, modify, or discard their existing social controls in favor of what they perceive as the attractive or even "glamorous" attributes of gang membership.…”
Section: Running Head: Street Gangs Theory Researchmentioning
confidence: 99%
“…They emit a coercive power (threat or use of force and violence) and a power to pay, buy, impress, and delegate status to members (Knox, 1994). As a result, young boys look up to gang members, mimic them, and aspire to gang membership (Hughes & Short, 2005). Media portraits of gangs such as gang films depicting characters rewarded for gang-like behaviors act as a blueprint for young aspiring gang members (Przemieniecki, 2005) and youth living in a culture that strongly identifies success with material wealth are particularly motivated to gang membership (Toy & Stanko, 2008).…”
Section: Becoming a Gang Member: Group Processesmentioning
confidence: 99%
“…Transgressions cannot go unpunished and reciprocation is perhaps the most common reason for gang violence (e.g. Hughes and Short 2005;Papachristos 2009) as gangs address a perceived wrong or block a threat. In turn, this helps gangs to save face, protect members and exact revenge on opponents (Papachristos, Hureau, & Braga, 2013).…”
Section: Intergroup Conflict and Status Enhancementmentioning
confidence: 99%
“…He found that structural patterns of social and economic disadvantage and racial inequality foster a community "street culture" that engenders violence (Anderson, 1999). Disadvantaged and unequal structures create a sense of pessimism and hopelessness in communities which leads to a culture that seeks to undermine and oppose mainstream norms (Bruce, Roscigno, & McCall, 1998;Hughes & Short, 2005;Kubrin & Weitzer, 2003;Melynk et al, 2010). This neighborhood culture has a great influence on individual behavior (Anderson, 1999); therefore, a community's opposition to mainstream norms emphasizes the importance of acquiring and maintaining the respect of others in the community is accomplished by demonstrating toughness and retribution for wrongs using violence (Anderson, 1999;Melynk et al, 2010).…”
Section: Impact Of Social Norms On Youth Violencementioning
confidence: 99%